215k views
0 votes
Emily is solving the equation 2(x+9)=4(x+7)+2. Her step are shown.

Click on the first step in which Emily made an error.

A. Step 1: 2(x+9)=4(x+7)+2
B. Step 2: 2x+18=4x+28+2
C. Step 3: 2x+18=4x+26
D. Step 4: -8x=2x
E. Step 5: -4=x

Also explain why answer B is wrong. <3

1 Answer

6 votes

Answer:

C. Step 3: 2x + 18 = 4x + 26

Explanation:

Step 1: Write equation

2(x + 9) = 4(x + 7) + 2

Step 2: Solve for x

  1. Distribute: 2x + 18 = 4x + 28 + 2
  2. Combine like terms: 2x + 18 = 4x + 30

Here we see that Emily made a mistake here. Instead of adding 2 to 28 and getting 30, Emily subtracted 2 from 28 to get 26. Hence, our answer should be C.

User CoryG
by
4.9k points